Dietary tryptophan supplementation induces a transient immune enhancement of gilthead seabream (Sparus aurata) juveniles fed fishmeal-free diets - Ramos-Pinto, Lourenco (2020)
European aquaculture is an industry with a high sustainability profile contributing to the supply of safe seafood. However, several diseases can affect farmed fish and it is imperative to find alternatives for chemotherapeutic treatments when disease outbreaks occur. Maintenance of health through nutrition is well-establish in modern animal farming, and amino acids (AA) are promising candidates as functional additives to improve fish health. Therefore, the goal of this research is to provide a better understanding of the influence of tryptophan supplementation on nutritional condition and immune mechanisms in fish. Triplicate groups of fish (13.3 +/- 0.3g) previously fed with a fishmeal-based diet were either fed a control diet with an extreme formulation (0% fishmeal) but meeting the AA requirements (CTRL), or the SUP diet, formulated as the CTRL with an increase in tryptophan (TRP) content. After 2 and 13 weeks of feeding, head-kidney (HK), liver (L) and white skeletal muscle (WSM) were collected for gene expression, whereas plasma was suited for humoral immune parameters. A holistic approach using transcriptomic, humoral and zootechnical parameters was undertaken. The expression of 29-31 genes for WSM, L or HK confirms an effect due to the treatment across time. A two-way ANOVA analysis revealed that 15-24 genes varied significantly depending on the tissue, and the multivariate analysis by means of PLS-DA explained (R-2) and predicted (Q(2)) with four components up to 93% and 78% of total variance, respectively. Component 1 (R-2 = 50.06%) represented the time effects, whereas components 2 (24.36%) and 3 (13.89%) grouped fish on the basis of dietary treatment, at early sampling. The HK results in particular suggest that fish fed SUP diet displayed an immunostimulated state at 2 weeks. No major differences were observed in plasma humoral parameters, despite an increase in antiprotease and peroxidase activities after 13 weeks regardless of dietary treatment. These results suggest that tryptophan supplementation may improve the seabream immune status after 2 weeks. Hence, the use of functional feeds is especially relevant during a short-term feeding period before a predictable stressful event or disease outbreak, considering that these putative advantageous effects seem to disappear after a 13 weeks feeding period.